Child buccal telomere length and mitochondrial DNA content as biomolecular markers of ageing in association with air pollution. (February 2021) - Hautekiet, Pauline; Nawrot, Tim S.; Janssen, Bram G.; Martens, Dries S.; De Clercq, Eva M.; Dadvand, Payam; Plusquin, Michelle; Bijnens, Esmée M.; Saenen, Nelly D.
Graphical abstract: Highlights: Chronic exposure to PM2.5 is associated with lower child buccal telomere length. Chronic exposure to PM2.5 is associated with lower child mitochondrial DNA content. Recent traffic related air pollution is associated with lower child telomere length. Abstract: Background: Pro-inflammatory conditions such as air pollution might induce biological ageing. However, the available evidence on such an impact in children is still very scarce. We studied in primary schoolchildren the association of ambient residential air pollution exposure with telomere length (TL) and mitochondrial DNA content (mtDNAc), two important targets of the core axis of ageing. Methods: Between 2012 and 2014, buccal TL and mtDNAc were repeatedly assessed using qPCR in 197 Belgian primary schoolchildren (mean age 10.3 years) as part of the COGNAC study. At the child's residence, recent (week), sub-chronic (month) and chronic (year) exposure to nitrogen dioxide (NO2 ), particulate matter ≤ 2.5 µm (PM2.5 ) and black carbon (BC) were estimated using a high resolution spatiotemporal model. A mixed-effects model with school and subject as random effect was used while adjusting for a priori chosen covariates. Results: An interquartile range (IQR) increment (1.9 µg/m 3 ) in chronic PM2.5 exposure was associated with a 8.9% (95% CI: −15.4 to −1.9%) shorter TL. In contrast to PM2.5, chronic exposure to BC and NO2 was not associated with TL but recent exposure to BC and NO2 showed significant inverse associations with TL: an IQR increment in recent exposure to BC (0.9 µg/m 3 ) and NO2 (10.2 µg/m 3 ) was associated with a 6.2% (95% CI: −10.6 to −1.6%) and 6.4% (95% CI: −11.8 to −0.7%) shorter TL, respectively. Finally, an IQR increment in chronic PM2.5 exposure was associated with a 12.7% (95% CI: −21.7 to −2.6%) lower mtDNAc. However, no significant associations were seen for NO2 and BC or for other exposure windows. Conclusion: Chronic exposure to PM2.5 below the EU threshold was associated with child's shorter buccal TL and lower mtDNAc, while traffic-related pollutants (BC and NO2 ) showed recent effects on telomere biology. Our data add to the literature on air pollution-induced effects of TL and mtDNAc, two measures part of the core axis of cellular ageing, from early life onwards.